(untitled) (Federal University Gusau Faculty of Education Journal, 2026)
This study examined the influence of teachers’ gender bias on classroom participation patterns among adolescents in public secondary schools in Lagos State, Nigeria. Using a descriptive correlational survey design, a total of 480 students (240 males and 240 females) and 48 teachers were selected through multistage sampling from eight public secondary schools. Data were collected using a Teachers’ Gender Bias Questionnaire, a Classroom Participation Scale, and structured classroom observations, and were analysed using descriptive statistics, independent samples t-tests, and Pearson correlation, complemented by qualitative thematic analysis. Findings revealed that teachers exhibited multiple forms of gender bias, including calling on boys more frequently, assigning cognitively demanding tasks to male students, and praising girls primarily for compliance or neatness. Male students participated significantly more than female students in classroom activities, while female students often self-censored or participated indirectly. A strong positive correlation was found between teachers’ gender bias and boys’ participation, and a strong negative correlation with girls’ participation. Qualitative data further highlighted how classroom interactions reinforced gendered expectations and shaped students’ confidence and engagement. The study concludes that teachers’ gendered practices significantly influence adolescents’ classroom participation, perpetuating gender hierarchies, and recommends targeted teacher training, inclusive classroom strategies, and policy interventions to promote equitable participation.